Toll-Like Receptor 4 Mediates Methamphetamine-Induced Neuroinflammation through Caspase-11 Signaling Pathway in Astrocytes - Du, Si-Hao; Qiao, Dong-Fang; Chen, Chuan-Xiang; Chen, Si; Liu, Chao; Lin, Zhoumeng; Wang, Huijun; Xie, Wei-Bing (Frontiers in Molecular Neuroscience, 2017)
Methamphetamine (METH) is an amphetamine-typed stimulant drug that is increasingly being abused worldwide. Previous studies have shown that METH toxicity is systemic, especially targeting dopaminergic neurons in the central nervous system. However, the role of neuroinflammation in METH neurotoxicity remains unclear. We hypothesized that Toll-like receptor 4 (TLR4) and Caspase-11 are involved in METH-induced astrocyte-related neuroinflammation.We tested our hypothesis by examining the change of TLR4 and Caspase-11 protein expression in primary cultured C57BL/6 mouse astrocytes and in the midbrain and striatum of mice exposed to METH with Western blot and double immunofluorescence labeling. We also determined the effects of blocking Caspase-11 expression with wedelolactone (a specific inhibitor of Caspase-11) or siRNA on METH-induced neuroinflammation in astrocytes. Furthermore, we determined the effects of blocking TLR4 expression with TAK-242 (a specific inhibitor of TLR4) or siRNA on METH-induced neuroinflammation in astrocytes.METH exposure increased Caspase-11 and TLR4 expression both in vitro and in vivo, with the effects in vitro being dose-dependent. Inhibition of Caspase-11 expression with either wedelolactone or siRNAs reduced the expression of inflammasome NLRP3 and pro-inflammatory cytokines. In addition, blocking TLR4 expression inhibited METH-induced activation of NF-κB and Caspase-11 in vitro and in vivo, suggesting that TLR4-Caspase-11 pathway is involved in METH-induced neuroinflammation.These results indicate that Caspase-11 and TLR4 play an important role in METH-induced neuroinflammation and may be potential gene targets for therapeutics in METH-caused neurotoxicity.